Maternal and Fetal Outcomes in Pregnant Women with Cardiac Disease - Zubaida Khanum, Nayab Hakim, Asma Hameed, Beenish Salam, Noreen Tahir, Sajida Asghar (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: To determine the adverse maternal and fetal outcomes in pregnant women presented with cardiac disease. Study Design: Cross-sectional study Place and Duration: Department of Gyne & Obs Khalifa Gulnawaz Teaching Hospital Bannu and Gyne Department Mardan Medical Complex MTI, Mardan during from the period Jan 2023 to June 2023. Material and methods: Total 120 pregnant women were enrolled in this study. Patients were aged between 20- 45 years. Patients detailed demographics were recorded after taking written consent. Among all the patients, 60 patients had cardiac disease and 60 had no cardiac disease. Two groups were maintained. Baseline characteristics such as age, parity, nature of cardiac lesions, New York Heart Association (NYHA) classification, and associated comorbidities were documented. Investigations included echocardiography, electrocardiography, and blood tests. Frequency of pre-eclampsia, gestational diabetes mellitus and post-partum haemorrhage were calculated. Adverse outcomes among (cesarean section, instrumental delivery,induction of labor and prolong labor, hypertensive disorder) were calculated among both groups. Fetal outcomes Perinatal mortality, Low birth weight, Low Apgar score and NICU admission were observed. Complete data was analyzed by SPSS 22.0 version. Results: Mean age of the patients in cardiac disease group was 30.45±4.58 years with mean BMI 23.46±4.74 Kg/m2 and in patients with no cardiac disease mean age was 28.86±6.48 years with mean BMI 22.85±5.78 Kg/m2. RHD was the most frequent type of heart disease found in 40 (66.67%). Maternal complications such as pre-eclampsia, gestational diabetes mellitus, postpartum hemmorhagen C-section were more in cardiac patients as compared to patients with no cardiac disease. Fetal outcomes such as perinatal mortality in cardiac group was found in 8 (13.33%) and in other group it was found in 1 (1.67%), low birth weight in cardiac group was found in 20 (33.33%) and in other group it was found in 8 (13.33%), low apgar score in cardiac group was found in 12 (16.67%) and in no other group it was found in 3 (5%), 14 (23.33%) in cardiac patients had NICU admission and 4 (6.67%) patient in healthy group admitted to NICU. Conclusion: We concluded in this study that the pregnant women with cardiac disease had high risk of adverse maternal and fetal complications. Keywords: Cardic Disease, Pre-eclampsia, Post-partum haemorrhage, C-section, Maternal Mortality, Perinatal Mortality, NICU Admission, Low Apgar Score